2009
DOI: 10.1111/j.1365-2133.2009.09186.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene-wide association study between the aromatase gene (CYP19A1) and female pattern hair loss

Abstract: These findings suggest that the common rs4646 C allele, which has been associated previously with higher circulating oestrogen levels, might be associated with predisposition to FPHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(107 citation statements)
references
References 42 publications
2
93
2
3
Order By: Relevance
“…While the findings of Yip et al [15] pointed out that the rs4646 allele positively correlates with FPHL in Caucasian patients, our study showed that there was no statistical significance for the expression of rs4646 between the FPHL patient group (A = 111 and C = 289) and the control group (A = 116 and C = 284, p = 0.695). Additionally, consistent with the negative results of the study of Redler et al [28] on the CYP19A1 gene of rs4646 in British and German FPHL patients, we demonstrated that there is no statistically significant difference (p = 0.871) in the gene pattern between our tested FPHL patient group (AA = 16, AC = 79, and CC = 105) and the control group (AA = 16, AC = 84, and CC = 100).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…While the findings of Yip et al [15] pointed out that the rs4646 allele positively correlates with FPHL in Caucasian patients, our study showed that there was no statistical significance for the expression of rs4646 between the FPHL patient group (A = 111 and C = 289) and the control group (A = 116 and C = 284, p = 0.695). Additionally, consistent with the negative results of the study of Redler et al [28] on the CYP19A1 gene of rs4646 in British and German FPHL patients, we demonstrated that there is no statistically significant difference (p = 0.871) in the gene pattern between our tested FPHL patient group (AA = 16, AC = 79, and CC = 105) and the control group (AA = 16, AC = 84, and CC = 100).…”
Section: Discussioncontrasting
confidence: 98%
“…In other studies, no association was found between steroid 5α-reductase isoform genes or sex steroid hormone receptors and FPHL [27]. Moreover, an Australian genome-wide association study suggested that the aromatase gene (CYP19A1) may contribute to FPHL, but this was not confirmed in another study [15,28]. …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…On the basis of a report of elevated aromatase levels in the skin of women with FPHL (23), androgens are assumed to act via a distinct mechanism, in contrast to male AGA. Aromatase, which is encoded by CYP19A1, converts androgens to oestrogens in the scalp hair follicles (24). Yip et al (24) performed a gene-wide association study of FPHL and CYP19A1 and reported borderline association for three variants.…”
Section: Introductionmentioning
confidence: 99%
“…2 Testosterone is converted to DHT with the help of the enzyme 5α-reductase. Deficiency of this enzyme has been implicated in the development of AGA.…”
Section: Introductionmentioning
confidence: 99%